The Impact Of Technical Efficiency On Firms’ Value: The Case Of The Halal Food And Beverage Industry In Selected Countries - Sylva Alif Rusmita; Siti Zulaikha; Nur Syazwani Mazlan; Nuradli Ridzwan Shah Bin Mohd Dali; Eko Fajar Cahyono; Indria Ramadhani (Plos One, 2024)
Indexed by Scopus/ERA